Convergence of income across regencies in Central Java: spatial econometric approach - Edy Yusuf Agung Gunanto; Mulyo Hendarto; Salman Fathoni (Program Magister Ilmu Ekonomi Pascasarjana Universitas Jambi, 2023)
The development of an economy is oriented towards not only growth but also equality. Furthermore, economic interaction across regions has to be captured in a development analysis to avoid the possibility of biased results. This study analyzes Central Java, Indonesia's economic development, by considering spatial interactions across regencies. The Spatial Durbin Model (SDM) is used for the analysis. The results show significant spatial interaction across regencies/cities in Central Java in the spatial model and economic convergence that occurs faster than in the non-spatial model. Then, the mismatch between the curriculum of education and industry needs is a presumption illustrated in the insignificant relationship of human capital to income. And an anomaly occurs where physical capital has a negative impact on income.